Mental health of non-binary youth: a systematic review and meta-analysis - Diana Klinger; Sofia-Marie Oehlke; Stefan Riedl; Ken Eschbaum; Heidi Elisabeth Zesch; Andreas Karwautz; Paul L. Plener; Oswald D. Kothgassner (BMC, 2024)
Abstract Background Non-binary identities are increasingly recognized within the spectrum of gender diversity, yet there is a dearth of research exploring the mental health challenges specific to this population. Therefore, this systematic review and meta-analysis aimed to comprehensively assess the mental health outcomes of non-binary youth in comparison to their transgender and cisgender peers. Methods A systematic search was conducted to identify relevant studies across three electronic databases (PubMed, Scopus, Web of Science) covering the period from inception to October 2023. The meta-analysis was performed employing a random-effects model. Inclusion criteria encompassed studies comparing non-binary youth with transgender or cisgender youth, providing data on mental health outcomes such as general mental health, depressive and anxiety symptoms, self-harm and suicidality. Results Twenty-one studies, meeting the inclusion criteria and originating from six different countries, were included in the analysis. The sample encompassed 16,114 non-binary, 11,925 transgender, and 283,278 cisgender youth, with ages ranging from 11 to 25 years. Our meta-analysis revealed that non-binary youth exhibit significantly poorer general mental health compared to both transgender (d = 0.24, 95% CI, 0.05-0.43, p =.013) and cisgender youth (d = 0.48, 95% CI, 0.35-0.61, p <.001), indicating a more impaired general mental health in non-binary youth. Regarding depressive symptoms, when comparing non-binary and cisgender individuals, a moderate and significant effect was observed (d = 0.52, 95% CI, 0.41-0.63, p <.001). For anxiety symptoms, a small but significant effect was observed in the comparison with cisgender individuals (d = 0.44, 95% CI, 0.19-0.68, p =.001). Furthermore, non-binary individuals exhibited lower rates of past-year suicidal ideation than transgender peers (OR = 0.79, 95% CI, 0.65-0.97, p =.023) and higher rates of lifetime suicidal ideation than cisgender youth (OR = 2.14, 95% CI, 1.46-3.13, p <.001). Conclusion Non-binary youth face distinct mental health challenges, with poorer general mental health, elevated depressive and anxiety symptoms compared to cisgender, and similar rates of self-harm and suicidal behavior compared to transgender individuals. These findings underscore the urgent need for targeted interventions, including gender-affirming mental health support, to address the specific needs of non-binary youth.